SYMBOLISM IN HANYA YANAGIHARA’S NOVEL A LITTLE LIFE: NEW CRITICISM - Fernandes, Khatrine Patricia; Yeni, Marliza (LingoLitera, 2026)
A Little Life is a novel by Hanya Yanagihara published in 2015. The novel describes how traumatic experiences in the past significantly affect the mental and physical condition of the main character, Jude. This study aims to identify the symbols that form an organic unity in the development of the novel's central themes. This research uses the close reading method with the New Criticism approach introduced by John Crowe Ransom. The results of the analysis show that there are various important symbols in the novel that collectively reinforce the themes and messages conveyed. These include scars, razors, books, mirrors, wheelchairs, ice cream, Willem's presence, blood, the color brown, bathrooms, paintings, long-sleeved clothes, and Jude himself. All these symbols are interconnected and work in concert to build an organic unity in the literary work, which ultimately reinforces the main themes of trauma, resilience, queer suffering, and friendship.